Direct costs and cost-effectiveness of dual-source computed tomography and invasive coronary angiography in patients with an intermediate pretest likelihood for coronary artery disease. Issue 6 (16th August 2011) - Dorenkamp, Marc; Bonaventura, Klaus; Sohns, Christian; Becker, Christoph R; Leber, Alexander W
Abstract : Aims: The study aims to determine the direct costs and comparative cost-effectiveness of latest-generation dual-source computed tomography (DSCT) and invasive coronary angiography for diagnosing coronary artery disease (CAD) in patients suspected of having this disease. Methods: The study was based on a previously elaborated cohort with an intermediate pretest likelihood for CAD and on complementary clinical data. Cost calculations were based on a detailed analysis of direct costs, and generally accepted accounting principles were applied. Based on Bayes' theorem, a mathematical model was used to compare the cost-effectiveness of both diagnostic approaches. Total costs included direct costs, induced costs and costs of complications. Effectiveness was defined as the ability of a diagnostic test to accurately identify a patient with CAD. Results: Direct costs amounted to €98.60 for DSCT and to €317.75 for invasive coronary angiography. Analysis of model calculations indicated that cost-effectiveness grew hyperbolically with increasing prevalence of CAD. Given the prevalence of CAD in the study cohort (24%), DSCT was found to be more cost-effective than invasive coronary angiography (€970 vs €1354 for one patient correctly diagnosed as having CAD). At a disease prevalence of 49%, DSCT and invasive angiography were equally effective with costs of €633. Above a threshold value of disease prevalence of 55%, proceeding directly to invasive coronary angiography was more cost-effective than DSCT. Conclusions: With proper patient selection and consideration of disease prevalence, DSCT coronary angiography is cost-effective for diagnosing CAD in patients with an intermediate pretest likelihood for it. However, the range of eligible patients may be smaller than previously reported.